Frindle - Clements, Andrew; Selznick, Brian (Turtleback Books St. Louis, MO, 2014)
When he decides to turn his fifth grade teacher's love of the dictionary around on her, clever Nick Allen invents a new word and begins a chain of events that quickly moves beyond his control